2018
DOI: 10.1111/imb.12516
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of CYP4G11—a highly conserved enzyme in the western honey bee Apis mellifera

Abstract: Determining the functionality of CYP4G11, the only CYP4G in the genome of the western honey bee Apis mellifera, can provide insight into its reduced CYP4 inventory. Toward this objective, CYP4G11 transcripts were quantified, and CYP4G11 was expressed as a fusion protein with housefly CPR in Sf9 cells. Transcript levels varied with age, task, and tissue type in a manner consistent with the need for cuticular hydrocarbon production to prevent desiccation or with comb wax production. Young larvae, with minimal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 63 publications
2
27
0
1
Order By: Relevance
“…The B. germanica genome contains only one CYP4G gene, and we have found that it plays a role in hydrocarbon production. Likewise, Acyrthosiphon pisum CYP4G51 and Apis mellifera CYP4G11 , the only CYP4G member in each species, have also been shown to be involved in hydrocarbon biosynthesis . We hypothesize that if only one CYP4G member is found in a given species it would at least participate in hydrocarbon biosynthesis.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The B. germanica genome contains only one CYP4G gene, and we have found that it plays a role in hydrocarbon production. Likewise, Acyrthosiphon pisum CYP4G51 and Apis mellifera CYP4G11 , the only CYP4G member in each species, have also been shown to be involved in hydrocarbon biosynthesis . We hypothesize that if only one CYP4G member is found in a given species it would at least participate in hydrocarbon biosynthesis.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike the B. germanica CYP4G19 that appears to be an abdominal oenocyte‐specific expression, CYP4G11 and CYP4G51 also showed highly abdomen‐independent expression . The expression of CYP4G11 in forager antennae was recently linked to the clearance of pheromonal aldehydes . That is, although CYP4G s are highly conserved in participating in hydrocarbon biosynthesis, the importance of this pathway in different species may confer upon CYP4G s a diversity of biologically important roles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations